(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2021)
Drawing on a typology of different ways in which power is exercised, this article makes the argument that given the distinctive understanding of the human subject as an interrelated person in existential therapy, there follows a distinctive understanding of how power can be conceived and positively exercised in the therapy relationship.